2019
DOI: 10.1186/s13567-019-0631-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a recombinant Newcastle disease virus-vectored vaccine for infectious bronchitis virus variant strains circulating in Egypt

Abstract: Infectious bronchitis virus (IBV) causes a major disease problem for the poultry industry worldwide. The currently used live-attenuated vaccines have the tendency to mutate and/or recombine with circulating field strains resulting in the emergence of vaccine-derived variant viruses. In order to circumvent these issues, and to develop a vaccine that is more relevant to Egypt and its neighboring countries, a recombinant avirulent Newcastle disease virus (rNDV) strain LaSota was constructed to express the codon-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 53 publications
(71 reference statements)
1
30
0
Order By: Relevance
“…Thus, it is necessary to develop a novel bivalent vaccine protect against NDV and IBV. In recent decades, attempts have been made to develop recombinant vaccines using NDV [48][49][50], adenovirus [51], duck enteritis virus [52], and avian metapneumovirus [53] viral backbones expressing the S1 or S2 portion of the IBV spike gene with differing levels of protection from IBV challenge. Among them, the NDV vector shows great promise due to its excellent characteristics, such as rapid and long-lasting immune response, low production costs, convenience of administration, and genetic stability [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is necessary to develop a novel bivalent vaccine protect against NDV and IBV. In recent decades, attempts have been made to develop recombinant vaccines using NDV [48][49][50], adenovirus [51], duck enteritis virus [52], and avian metapneumovirus [53] viral backbones expressing the S1 or S2 portion of the IBV spike gene with differing levels of protection from IBV challenge. Among them, the NDV vector shows great promise due to its excellent characteristics, such as rapid and long-lasting immune response, low production costs, convenience of administration, and genetic stability [45].…”
Section: Discussionmentioning
confidence: 99%
“…Abozeid et al [50] reported a similar design strategy as that of Shirvani et al [48] but modified the IBV S protein and rescued three recombinant LaSota strains. Immune-protection experiments show that candidate vaccines can alleviate the severity of clinical symptoms but does not reduce virus shedding.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Abozeid, H.H. et al ( [88]) showed that recombinant NDV expressing codon-optimized S glycoprotein of the Egyptian IBV variant strain IBV/Ck/EG/CU/4/2014 provided excellent protection against both NDV and IBV challenge in chicken. Thus, rNDV is an efficient vector for the delivery of IBV-specific immunogens in chickens.…”
Section: Engineered Ndv As a Bivalent Vaccine In Poultrymentioning
confidence: 93%
“…34]. Despite wide spread vaccination with classical and/or variant strain based vaccines in Egypt, IBV outbreaks were frequently reported in vaccinated and non-vaccinated flocks of farms [16], indicating poor protection against the prevalent local variant strain [35].…”
Section: Discussionmentioning
confidence: 99%